An optimal scheduling strategy for integrated electric-thermo-hydrogen energy system considering demand response uncertainty - ZHANG Haiwei; LIU Huijia; HONG Jiaen; XU Zhigao (Zhejiang dianli)
To enhance the operational flexibility of community integrated energy systems （IES） and fully explore their scheduling potential， an optimal scheduling strategy for integrated electricity-heat-hydrogen energy systems considering demand response uncertainty is proposed. First， a electrolytic hydrogen production unit with variable load startup-shutoff characteristics is introduced， enabling refined hydrogen utilization unit modeling based on their two-stage operation process and operational characteristics of electricity-hydrogen coupling. Second， an uncertainty model for substitutive demand response is developed using consumer psychology theory and a logistic regression curve. Third， an incentive policy is designed and combined with price-based demand response to optimize user load curves. Finally， simulation results validate the effectiveness of the proposed strategy， demonstrating its ability to promote renewable energy consumption and reduce operating costs of the system.